PENGGUNAAN DANA DESA DI WILAYAH KECAMATAN SIGEDONG KABUPATEN MEMPAWAH PROVINSI KALIMANTAN BARAT DARI TAHUN 2019-2023 - Dwi Agus Sumarno (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2023)
Village Financial Management is a form of governance in the Village regarding the Revenue and Expenditure Budget in order to carry out development based on priority activities that have been determined in the Village Conference. Management of village funds by using management functions through the principles of good public service will be able to measure the development of villages in Segedong District starting from the calculation of the Fiscal Year from Transfers to Regions in 2019 to 2023. Therefore, this research aims to examine the use of Village Funds in the Sigedong District, Mempawah Regency, West Kalimantan Province from 2019-2023. The author uses a qualitative descriptive research method with an inductive approach because the researcher wants to get clear and know how the evaluation of Village Fund Utilization will start from 2019-2023. From the results of research on six villages in the Segedong sub-district area, it is known that the participatory development carried out by the village community in the Segedong sub-district has been running well and correctly resulting in development that is in accordance with the applicable mechanisms and regulations. The implementation of activities by the village government together with the community is carried out using Swakelola and has produced measurable and quality activities. The capacity of the apparatus is increasing by being given the opportunity to learn to increase government knowledge, skills and public service and knowledge of electronic communications technology. The results of the development can be used as a basis for submitting a Development Village Index to the government to make it an independent village in accordance with the targets of the Mempawah Regency.